Anti-Herpes Simplex Virus (Wild-Type and Drug-Resistant) Properties of Herbal KerraTM, KSTM, and MinozaTM - Chaleampol Loymunkong; Kiattawee Choowongkomon; Chukkris Heawchaiyaphum; Nutchanat Chatchawankanpanich; Chamsai Pientong; Tipaya Ekalaksananan; Jureeporn Chuerduangphui (Viruses)
Commercial herbal compounds are a main attractive target to explore for a novel drug for the treatment of HSV. This study investigated the anti-HSV infectivity of extracts derived from the Thai commercial herbals KerraTM, KSTM, and MinozaTM. Wild-type HSV-1 KOS, HSV-2, and drug-resistant HSV-1 dxpIII were used to investigate any inhibitory effects of these extracts. A plaque formation assay was performed to investigate the effects of all extracts. The viral ICP4, UL30, gD, and gB and cellular IL1β, IL6, STAT3, and NFKB1 expression levels were evaluated. The KerraTM, KSTM, and MinozaTM extracts at 50–200 μg/mL significantly inhibited HSV-1 KOS and dxpIII infection in the post-entry step, whereas only MinozaTM could not reduce plaque formation of HSV-2. In addition, ICP4, UL30, and gD mRNAs and gB protein were significantly decreased in KerraTM- and KSTM-treated cells. Furthermore, IL1B, IL6, STAT3, and NFKB1 expression was upregulated in KerraTM- and KSTM-treated cells. KerraTM and KSTM could be agents against HSV infection, especially the HSV acyclovir (ACV)-resistant strain. From the docking result and drug-likeness prediction, 2-Methoxy-9H-xanthen-9-one, piperine, and sargassopenilline D found in KerraTM, KSTM, and MinozaTM show high binding energy closely resembling ACV, and are desirable as drug-like characteristics.